2023
DOI: 10.1007/s00784-023-04873-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatments as an adjunct to non-surgical periodontal therapy in subjects with periodontitis and type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: Objectives Periodontal disease and diabetes have an extensively investigated bidirectional correlation. Non-surgical periodontal treatment (NSPT) was proven to contribute to glycemic control. Moreover, it may benefit from the association of adjunctive therapies. The aim of the present systematic review is to assess the clinical efficacy of NSPT in association with laser (LT) or photodynamic therapy (PDT) in controlled or uncontrolled diabetic patients, and to grade the level of evidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Corbella et al . [ 24 ] in a systematic review and meta-analysis, has reported additional benefits of PDT in deep periodontal pockets as well as a higher decrease in HbA1c levels at 3 months, but no significant difference was noted at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Corbella et al . [ 24 ] in a systematic review and meta-analysis, has reported additional benefits of PDT in deep periodontal pockets as well as a higher decrease in HbA1c levels at 3 months, but no significant difference was noted at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The LASER revolution in dentistry and the invention of ruby LASER by Theodore Maiman in 1960 has seen significant changes over the past few decades owing to advances and usability of LASERs in a multitude of dental and periodontal applications (Passanezi et al, 2015;Theodoro et al, 2021;Corbella et al, 2023). LASERs are clinically categorized into two types based on their wavelength: 1) a deeply penetrating type where the LASER light penetrates and scatters into the tissue deeply, such as the diode LASERs (810-980 nm) and neodymium-doped yttrium-aluminum-garnet (Nd:YAG) available for clinical application; and 2) a superficially absorbed type such are the erbium-doped yttrium-aluminum-garnet (Er:YAG) (2940 nm), carbon dioxide (CO 2 ) (10,600 nm) and erbium, chromium: yttrium-scandium-gallium-garnet (Er, Cr: YSGG) (2780 nm) LASERs (Ohsugi et al, 2020;Fu and Wo, 2021).…”
Section: Lasersmentioning
confidence: 99%